Does institutional entrenchment shape instrument adjustment?: Assessing instrument constituency influences on American and Australian motor fuel taxation. Issue 1 (2nd January 2018) - Perl, Anthony; Burke, Matthew I.
Abstract: This article compares the long-run adjustment of transport finance instruments in the US and Australia. Change and continuity in these policy instruments highlights how the institutional context can influence an instrument constituency's influence within a policy subsystem. In the US, a mature instrument constituency created and entrenched motor fuel taxes as an exclusive resource for implementing transport policy. In Australia, fuel taxes remained exposed to the politics of inter-governmental competition and fiscal rivalry across subsystems, leaving less opportunity for instrument constituency leverage. We explore the circumstances under which instrument constituencies can either constrain or facilitate adjusting transportation policy through fiscal mechanisms, especially when the efficacy of established instruments appears to decline. The policy paradigm of American transportation rests upon the entrenched segregation of fuel tax revenues for infrastructure spending. When fuel tax revenues grew from the 1980s until 2008, transportation policy yielded an expanding stream of programme outputs – building the interstate highway network and upgrading part of the nation's urban transit infrastructure. The instrument constituency that shaped the Highway Trust Fund found a privileged position within the transportation subsystem. In Australia, similar instruments have not been entrenched and have thus been open to political influences beyond the subsystem. The effects of institutional configuration on instrument constituency participation in policy change become most apparent during times of austerity, or when fiscal instruments fail to deliver expected revenues. Electrification of vehicle fleets is now creating such disruption in the transportation subsystem.